The structure, properties and rheological characterisation of exopolysaccharides produced by Chryseobacterium cucumeris AP-2 from deteriorated milk. (March 2022) - Hu, Xin; Pan, Yaping; Bao, Mutai; Zhang, Xiuli; Luo, Chengyi; Han, Xiao; Li, Fengshu
Abstract: A novel exopolysaccharide (APS) was secreted by Chryseobacterium sp. AP-2. The yield of APS reached 3.247 g L −1 in MRS medium with 2% (w/v) maltose during 72 h incubation. The APS was a 4.871 × 10 5 Da heteropolysaccharide with rhamnose, fucose, mannose, glucose and galactose; using Fourier transform infrared spectroscopy, the main groups in APS were found to be hydroxyl and phosphate groups. APS exhibited a flaky structure with irregular holes, and its structural composition was confirmed by 1 H and 13 C nuclear magnetic resonance analysis. The degradation temperature (197.3 °C) of APS was determined by thermogravimetric analysis. APS exhibited stable emulsification property with the higher emulsification indexes (EI) than 50% in the diesel oil and kerosene. Ultimately, physicochemical factor (temperature, pH values and salts) had an impact on rheological properties of APS. The properties and structure characterisation of APS laid the experimental foundation for further exopolysaccharide exploration.